ANALISIS PERTANGGUNG JAWABAN KEUANGAN DALAM PERSPEKTIF PSAK NOMOR 45 UNTUK AKUNTABILITAS LAPORAN KEUANGAN PADA YAYASAN SEKOLAH DASAR RHEMA INDONESIA - Mulia Rahmah (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2019)
Transparency and accountability in the financial report is needed. Like business company, non-profit organizations also require transparency and accountability in the financial report. To promote transparency and accountability of nonprofit organizations financial report Indonesian Institute of Accountants has made PSAK No. 45 on non- profit organizations This study objective to identify and analyze the application of PSAK NO. 45 in preparing the financial report of the Yayasan Sekolah Dasar Rhema Indonesia. This study shows that Yayasan Sekolah Dasar Rhema Indonesia not prepare financial report based on PSAK No.45. Yayasan Sekolah Dasar Rhema Indonesia have limited human resources issues in preparing the financial report.